Detection of Novel Visible-Light Region Absorbance Peaks in the Urine after Alkalization in Patients with Alkaptonuria - Tokuhara, Yasunori (Public Library of Science, 2014)
BACKGROUND: Alkaptonuria, caused by a deficiency of homogentisate 1,2-dioxygenase, results in the accumulation of homogentisic acid (2,5-dihydroxyphenylacetic acid, HGA) in the urine. Alkaptonuria is suspected when the urine changes color after it is left to stand at room temperature for several hours to days; oxidation of homogentisic acid to benzoquinone acetic acid underlies this color change, which is accelerated by the addition of alkali. In an attempt to develop a facile screening test for alkaptonuria, we added alkali to urine samples obtained from patients with alkaptonuria and measured the absorbance spectra in the visible light region. METHODS: We evaluated the characteristics of the absorption spectra of urine samples obtained from patients with alkaptonuria (n = 2) and compared them with those of urine specimens obtained from healthy volunteers (n = 5) and patients with phenylketonuria (n = 3), and also of synthetic homogentisic acid solution after alkalization. Alkalization of the urine samples and HGA solution was carried out by the addition of NaOH, KOH or NH4OH. The sample solutions were incubated at room temperature for 1 min, followed by measurement of the absorption spectra. RESULTS: Addition of alkali to alkaptonuric urine yielded characteristic absorption peaks at 406 nm and 430 nm; an identical result was obtained from HGA solution after alkalization. The absorbance values at both 406 nm and 430 nm increased in a time-dependent manner. In addition, the absorbance values at these peaks were greater in strongly alkaline samples (NaOH- KOH-added) as compared with those in weakly alkaline samples (NH4OH-added). In addition, the peaks disappeared following the addition of ascorbic acid to the samples. CONCLUSIONS: We found two characteristic peaks at 406 nm and 430 nm in both alkaptonuric urine and HGA solution after alkalization. This new quick and easy method may pave the way for the development of an easy method for the diagnosis of alkaptonuria.